Immunophenotype of Normal and Myelomatous Plasma-Cell Subsets - Robillard, Nelly; Wuillème, Soraya; Moreau, Philippe; Bene, Marie C. (Frontiers in Immunology, 2014)
Plasma-cells are essentially characterized by the co-expression of CD138 and CD38, which allows their identification in flow cytometry in bone marrow, peripheral blood or cell suspensions from tissues. These terminally differentiated B-cells may lose the expression of surface CD19 and that of CD20 while retaining CD27. When malignant, they can gain a number of other markers such as CD28, CD33, CD56 or CD117 and lose CD27. Moreover, since each plasma cell is only able to produce a single type of immunoglobulins, they display isotypic restriction and clonal malignant plasma cells can be further characterized by their homogeneous expression of either kappa or lambda light chains. In multiple myeloma (MM), such plasma cell clones produce the immunoglobulin identified in plasma as an abnormal peak. In the bone marrow where they essentially accumulate, these plasma cells may however display various immunophenotypes. The latter were explored in a two-way approach. Firstly the various subsets delineated by the selective or common expression of CD19 together with combined CD56/CD28 were explored in normal and MM bone marrow. Then other aberrant markers’ expression was investigated, i.e. CD20, CD27, CD33, CD56, CD117. These data were compared to literature information. They underline the vast heterogeneity of MM plasma cells possibly accounting for the various answers to therapy of MM patients.